A.D. - Lofton, Saab (Gualala, CA : III Publishing, 1995)
The best case and worst case scenarios... 2030 A.D.: Louis Farrakhan's Nation of Islam and Tom Metzger's White Aryan Resistance have taken over America and divided the United States between them into racially segregated regimes. When one Fred Hampton Rush Senior is charged with sedition for rebelling against this new order, his sentence is to become a human guinea pig in a cryogenic experiment. Fred Rush Sr. is put into a state of suspended animation and does not awaken until... 2410 A.D.: A time when the world is governed by L.S.D., a Libertarian Socialist Democracy, and Fred is being guided through this utopian future by his direct male descendant, peace officer Captain Huey P. Rush. But as Fred is riding in flying cars and being introduced to aliens, something is happening. Something that could destroy everything mankind has worked so hard for... A menace from the past threatens the future..